THE CURRENT SITUATION OF SOCIAL MEDIA USE AMONG STUDENTS AT DONG NAI MEDICAL COLLEGE IN 2024. (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of social media use among students at Dong Nai Medical College in 2024.Subjects and research methods: Students studying at Dong Nai Medical College.Conclusion: Social networks have become an indispensable part of student life, Tiktok, zalo, facebook are social networks with a rate of students using regularly at 63.2%; 62.6% and 57.8%. Average use 1-3 hours/day, increasing on days off (at 5 hours/day).
Keywords: Behaviors, social media, student, Dong Nai Medical College